TANGGUNG JAWAB NEGARA TERHADAP PERLINDUNGAN PEJABAT DIPLOMATIK MENURUT KONVENSI WINA 1961 (CONTOH KASUS PENYERANGAN DUTA BESAR RUSIA DI TURKI) - Yonathan Yogy; Ida Kurnia (Fakultas Hukum Universitas Tarumanagara, 2018)
The establishment of diplomatic relations aims to strengthen a relationships between state. The establishment of diplomatic relations is based on mutual consent between two states. After consent has been reached, each state can dispatch members of the mission .The function of a member of the missions is to represent the sending state, to protect the interests of the sending state and its nationals, to negotiate, Ascertaining by all lawful means conditions and developments in the receiving State, and to promote friendly relations between the sending country and the receiving country. The Vienna Convention 1961 on diplomatic relations provides immunity and privilege to members of the missions in carrying out diplomatic functions . Such immunity and privilege are granted not for personal gain, it is provided to facilitate members of the missions in performing diplomatic functions. One of the forms of immunity is Inviolability. Inviolability of members of the missions is regulated by Article 29 of Vienna Convention 1961. Article 29 stated that the receiving state shall take appropriate measures to prevent any attack on members of the missions. But if the receiving state fails to protect the members of the missions, is there any legal consequence and state’s responsibility ?. The author is interested to raise the issue into a thesis.